MIRIKIZUMAB REDUCES ABDOMINAL PAIN IN PATIENTS WITH MODERATELY TO SEVERELY ACTIVE CROHN'S DISEASE. (22nd January 2022) - Loftus, Edward; Pollack, Paul; Hunter, Theresa; Shan, Mingyang; Chan, Lai-Shan; Deckard, Deanilee; Cross, Raymond
Abstract: BACKGROUND: Mirikizumab (miri), an anti-IL-23p19 inhibitor, has demonstrated efficacy in patients with ulcerative colitis and moderately to severely active Crohn's disease (CD) in a Phase 2, randomised, double-blind, placebo-controlled study (NCT02891226). This analysis evaluated the effect of miri versus placebo (PBO) on worst abdominal pain (AP) utilising an 11-point AP Numeric Reporting Scale (AP NRS). METHODS: During induction, patients were randomised 2:1:1:2 to receive PBO, 200mg, 600mg, or 1000mg miri administered intravenously (IV) every four weeks (Q4W). At week (W)12, patients entered a blinded maintenance treatment. Patients who received miri during induction and achieved ≥1 point improvement in Simple Endoscopic Score for Crohn's Disease (SES-CD) at W12 were randomised 1:1 to either continue induction treatment (IV 200mg, 600mg, 1000mg miri Q4W) or receive 300mg miri Q4W administered subcutaneously (SC) for 40W (maintenance). Because of small patient numbers, the randomised maintenance groups results were combined for those who continued the same IV induction treatment (All IV-C) and those who were randomised to SC treatment (All SC). SES-CD non-improvers (NI/1000mg IV Miri) and patients who received PBO (PBO/1000mg IV Miri) during induction received 1000mg miri IV Q4W during maintenance. Patients recorded "worst AP in the past 24 hours" each day using an 11-point AP NRS (0=no pain to 10=worst possible pain) on an electronic diary. The Pain NRS is a valid, reliable, and responsive patient reported outcome that can be used to assess pain among patients with CD. Weekly average score was calculated and compared to placebo using a mixed model for repeated measures (MMRM) for visits in the induction period. Observed change in Pain NRS is presented for maintenance. RESULTS: Significant reduction in AP NRS was reported by patients treated with 600mg miri compared to patients treated with placebo at W8 (least square mean difference ± standard error [95% confidence interval]: -1.01 ± 0.4 [-1.87, -0.14], p =0.02) (Table 1) and in all miri treatment groups: 200mg (-0.92 ± 0.4 [-1.80, -0.03], p =0.04), 600mg (-1.23 ± 0.4 [-2.11, -0.36], p =0.006) and 1000mg (-0.86 ± 0.4 [-1.57, -0.15], p =0.02) miri versus PBO at W12 (Table 1). Patients who received miri during induction continued to show improvements at W52 (Table 1). Patients treated with PBO/1000mg IV during maintenance reported similar improvements to patients who received miri from W0-52 (Table 1). CONCLUSION: Using an 11-point Abdominal Pain Numeric Reporting Scale, mirikizumab treatment was associated with statistically significant improvements in abdominal pain when compared to placebo after 12 weeks in patients with moderately to severely active Crohn's disease. Additional numeric reductions in abdominal pain were observed through 52 weeks in all mirikizumab treated patient groups.